(untitled) (Applied Biological Research, 2016)
The introduction of ZAT12 gene for drought tolerance into rice cv. ‘PR 116’was carried out through particle bombardment. Callus was induced on MS medium supplemented with 2,4-D(2.5 mg L-1) + kinetin (0.5 mg L-1) + proline (560 mg L-1) + sucrose (30 g L-1) + agar (8 g L-1). The embryogenic scutellar calli(10-12days old) were incubated on osmoticum medium for 4 hr followedby bombardment with isolated ZAT-12 DNA (1 µg µL-1). Next day morning bombarded calliweretransferredto the recoverymedium for 3 days to revive the growth followed by transfer onto the selection medium containing kanamycin (40 ppm). Percent selection recorded in genotype ‘PR116’ was 43.1% with the number of independent transgenicplants as 27.PCRanalysis confirmed the presence of transgene ZAT12 in 16 independent plants. These plants were grown to maturity in transgenic glass house. All the plants exhibited normal growth and development.